Urgensi Penggunaan Ganja Bagi Disabilitas Untuk Kepentingan Medis Ditinjau Dari Ius Constitutum - Saputra Marpaung, Agung Risky; Simangunsong, Frans (Indonesian Journal Publisher, 2023)
The purpose of writing this journal, to conduct research and describe the urgency of using class I Narcotics (cannabis) as a treatment therapy reviewed from the perspective of health law. This research uses normative legal research methods with a statue approach, conceptual approach, and case approach in which various related literature in this study as secondary data that will strengthen the research argumentation. The results showed that juridically the provisions of the use of medical cannabis categorised as Class I Narcotics for the purposes of medical services in Indonesia are specifically not regulated in the Health Law, but only limited to the regulation of narcotics in general as regulated in the Health Law. However, looking at the benefits and use value of medical cannabis that have been previously researched by experts abroad, it does not rule out the possibility for Indonesia in this case to also conduct further research on the benefits of medical cannabis as a treatment therapy.